Anthropozoonotic transmission of Monkeypox: Are our canine companions at risk? - Robinson, Jared; Banerjee, Indrajit; Leclézio, Alexandra (Nepal Mediciti Medical Journal, 2022)
Monkeypox is the latest zoonotic outbreak spreading in its majority throughout the Western region of the globe. The latest statistics and reports indicate that Spain, France, Germany, Portugal and the Netherlands are the country’s worst effected with a total of 7083, 3897, 3570, 845 and 1221 cases respectively. The WHO has also reported numerous cases extending into the Balkans and Turkey. The current global Monkeypox outbreak is becoming more concerning as the total number of cases globally has surpassed 35000, and the incident rates are accelerating with a 20% growth in cases being noted on a weekly basis. This global increase in cases intern enhances exposure of the virus to a larger portion of the populous; the exposure of the virus is not only intensified in humans but also their household pets and animals.